2023
DOI: 10.1002/wer.10893
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biogas production in anaerobic digestion of a full‐scale wastewater treatment plant using ensembled machine learning models

Abstract: Anaerobic digestion (AD) of sludge is a key approach to recover useful bioenergy from wastewater treatment and its stable operation is important to a wastewater treatment plant (WWTP). Because of various biochemical processes that are not fully understood, AD operation can be affected by many parameters and thus modeling AD processes becomes a useful tool for monitoring and controlling their operation. In this case study, a robust AD model for predicting biogas production was developed using ensembled machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
0
0
1
Order By: Relevance
“…Previous studies provided very limited knowledge on the effectiveness of ensemble machine learning in optimizing individual components of biogas production. The available research indicated its ability to improve the prediction of individual methods [45,46], which contradicts the results of this study. However, while several broader studies generally agreed on the effectiveness of ensemble machine learning, they also provided mixed observations regarding its robustness relative to individual methods.…”
Section: Resultscontrasting
confidence: 99%
“…Previous studies provided very limited knowledge on the effectiveness of ensemble machine learning in optimizing individual components of biogas production. The available research indicated its ability to improve the prediction of individual methods [45,46], which contradicts the results of this study. However, while several broader studies generally agreed on the effectiveness of ensemble machine learning, they also provided mixed observations regarding its robustness relative to individual methods.…”
Section: Resultscontrasting
confidence: 99%